Gene set enrichment analysis identifies immune subtypes of kidney renal clear cell carcinoma with significantly different molecular and clinical properties - Chen, Zuobing; Cao, Wenxiu; Luo, Jiangti; Abdelrahman, Zeinab; Lu, Qiqi; Wang, Huafen; Wang, Xiaosheng (Frontiers in Immunology, 2023)
Background Kidney renal clear cell carcinoma (KIRC) is the most common renal malignancy, characterized by high levels of tumor-infiltrating lymphocytes (TILs) and poor prognosis once metastasis. Multiple studies have shown that KIRC has a highly heterogeneous tumor microenvironment that is associated with significant differences in the efficacy of most first-line drugs for KIRC patients. Thus, a classification of KIRC based on the tumor microenvironment is significant, although such subtyping methods remain insufficient. Methods Based on gene set enrichment scores of 28 immune signatures, we hierarchically clustered KIRC and identified its immune subtypes. Furthermore, we comprehensively explored molecular and clinical characteristics of these subtypes, including survival prognosis, proliferation, stemness, angiogenesis, tumor microenvironment, genome instability, intratumor heterogeneity, and pathway enrichment. Results Cluster analysis identified two immune subtypes of KIRC, termed Immunity-High (Immunity-H) and Immunity-Low (Immunity-L), respectively. The clustering result was consistent across four independent KIRC cohorts. The Immunity-H subtype displayed higher levels of TILs, tumor aneuploidy, homologous recombination deficiency, stemness and proliferation potential, and worse survival prognosis. However, the Immunity-L subtype displayed higher intratumor heterogeneity and stronger angiogenesis signature than Immunity-H. Pathway enrichment analysis showed that the Immunity-H subtype was more enriched in immunological, oncogenic, and metabolic pathways, while the Immunity-L subtype was more enriched in angiogenic, neuroactive ligand-receptor interaction, and PPAR pathways. Conclusions KIRC can be classified into two immune subtypes based on the enrichment of immune signatures in the tumor microenvironment. Both subtypes display significantly distinct molecular and clinical features. Increased immune infiltration is associated with worse prognosis in KIRC. Immunity-H KIRC patients could have active responses to PPAR inhibitors and immune checkpoint inhibitors, while Immunity-L patients could have favorable responses to anti-angiogenic agents and immune checkpoint inhibitors. The immunological classification provides molecular insights into KIRC immunity, as well as clinical implications for the management of this disease.